Efficacy of Carbamide Peroxide Assisted by Er,Cr:YGSS Laser Induced Photoacoustic Streaming Technique for Enhancing the Color of Internally Stained Teeth - Wajeh, Aya Saad; Jawad, Hussein A. (Iraqi Journal of Laser, 2024)
Objective: To evaluate the impact of photon-induced photoacoustic streaming (PIPS) technique for enhancing tooth color changes using Er,Cr:YSGG (2780 nm) laser with carbamide peroxide. Materials and methods: A total of 42 sound premolars were included in this study. All teeth were endodontically treated then stained artificially utilizing sheep blood followed by placement of a 3mm layer of resin-reinforced GIC 2 mm apical to the CEJ on the buccal aspect. Such stained teeth were bleached conventionally with 37% carbamide peroxide or treated by PIPS using Er,Cr:YSGG laser ( 25 Hz frequency, 0.1 W power, 60 μs pulse duration ) with 37% carbamide peroxide. The results were evaluated after 1, 2, and 3 weeks, resulted color changes were measured by using a spectrophotometer. Results: Both techniques resulted in a significant color change at the endpoint of the study. However, intergroup comparison demonstrated that PIPS with 37% carbamide peroxide was significantly (p <0.05) more effective than walking bleaching using 37% carbamide peroxide in bleaching outcomes over all time intervals of the study. Conclusion: The current study showed that the PIPS technique used to activate bleaching agents containing 37% carbamide peroxide was more efficient in achieving desirable bleaching outcomes than the conventional walking-bleaching techniques.